Teknoloji transferi sözleşmeleri örneğinde götürü tazminat ve ceza koşulu hükümlerinin Anglo Sakson ve Türk hukuku perspektifinden değerlendirilmesi - Başar, Mükerrem Onur; Başar, Mükerrem Onur (Türk-Alman Üniversitesi, 2023)
Türkiye’nin de dâhil olduğu Kara Avrupası hukuk sistemi ile Anglo Sakson hukuk sistemi arasındaki yaklaşım farklılıkları, teknolojinin ve internetin gelişimi ile birlikte, özellikle teknoloji transferini konu alan ticari ilişkilerde kullanılan sözleşmelerde, daha da belirgin bir hal almaktadır. Her ikisi de sözleşme özgürlüğü prensibini esas almasına rağmen, Kara Avrupası hukuk sisteminin, sözleşmelerde ceza koşuluna yer verme hususundaki liberal yaklaşımı ile Anglo Sakson hukukunun ceza koşulunu yasaklayıcı bakış açısı, anılan iki hukuk sisteminin bu konudaki önemli bir yaklaşım farklılığını ortaya koymaktadır. Diğer yandan, Anglo Sakson hukukunda yer alan cezalandırıcı tazminat düzenlemelerine -kural olarak- Kara Avrupası hukuk sistemlerinde yer verilmiyor olması, iki hukuk sistemi arasında bu konuda mevcut olan önemli bir diğer ayrışmayı oluşturmaktadır.

The differences in approach between the Continental European legal system, including Turkey, and the Anglo-Saxon legal system, become more apparent with the development of technology and the internet, especially in contracts used in commercial relations on technology transfer. Although both are based on the principle of freedom of contract, the liberal approach of the Continental European legal system to include penal clauses in contracts and the prohibitive point of view of the Anglo-Saxon law on the penal clause reveal an important difference in approach in this regard. On the other hand, the fact that punitive compensation arrangements in Anglo Saxon law are not included in the Continental European legal systems as a rule, which constitutes another important divergence between the two legal systems in this regard.
Eine Bewertung der Schadensersatz- und Vertragsstrafeklauseln in Technologietransferverträgen aus der Sicht des angelsächsischen und türkischen Rechts
An assessment of liquidated damages and penalty clauses in the example of technology transfer agreements from the perspective of Anglo Saxon and Turkish law
Keywords: Teknoloji transferi sözleşmeleri; Ceza koşulu; Götürü tazminat; Cezalandırıcı tazminat; Technology transfer agreements; Penal clause; Liquidated damages; Punitive compensation